Synthesis of Semiconductor Zinc Sulfide Nanospheres for Improving Piezoresistive Sensing Behavior of Melt‐Mixed Poly(vinylidene fluoride)/Carbon Nanotube Composites - Müslüm Kaplan; Emre Alp; Beate Krause; Regine Boldt; Petra Pötschke (Advanced Materials Interfaces)
Abstract Studies have increasingly aimed at improving the piezoresistive behavior of polymer‐based conductive composites (CPCs) for strain‐sensing, with inorganic nanomaterial enhancement offering research opportunities. This study investigates the impact of incorporating zinc sulfide nanospheres (ZnS NSs, 1–7 wt.%), synthesized via a one‐step hydrothermal method, into a poly(vinylidene fluoride) (PVDF) polymer matrix together with multi‐walled carbon nanotubes (MWCNTs). Field emission scanning electron microscopy (FE‐SEM), energy‐dispersive X‐ray spectroscopy (EDX), and X‐ray diffraction (XRD) analyses reveal that ZnS NSs comprise a mixture of ZnS0.96O0.04 and S phases. While of ZnS NSs minimally impact tensile properties of the PVDF/MWCNT composites, they reduce elongation at break at 5 wt.%. During 15‐cycle strain sensing up to 3% strain, ZnS NSs‐enhanced composites outperformed PVDF/1 wt.% MWCNT. The reference sample's resistance change ratio (ΔR/R0) decreased below 1% with increased cycles, while 1 wt.% ZnS NSs increased ΔR/R0 to 3%, reducing changes upon cycle increments. Higher ZnS NSs levels (3–7 wt.%) resulted in ΔR/R0 exceeding 4–5%, indicating enhanced strain sensing performance. Fourier‐transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) showed limited impact of ZnS NSs on the thermal properties and microstructure of the composites.